Factors associated with HIV infection among Yi minority residents in Liangshan Prefecture, Sichuan Province: A path analysis. Issue 14 (April 2018) - Yang, Shujuan; Zhai, Wenwen; Pei, Rong; Jike, Chunnong; Nan, Lei; Yu, Gang; Liao, Qiang; Wang, Qixing; Liu, Danping; Gao, Bo; Xiao, Lin; Gong, Yuhan; et al.
Abstract : Abstract: We aimed to evaluate HIV prevalence among residents of Liangshan Prefecture through HIV sentinel surveillance (HSS) data over the period from 2010 to 2016, and investigate risk factors for HIV infection in this population and interactions among them. Two sites (Dechang and Ningnan counties) with majority-Han populations, and 1 site (Butuo) with a majority-Yi population were selected. We used questionnaires to investigate residents' demographic and behavioral characteristics from 2010 to 2016, and performed HIV testing. Multivariate logistic regression and path analysis were undertaken to investigate the interactions and mediating effects among significant risk factors for HIV infection. A total of 5403 community residents in the Yi area and 10, 897 community residents in the Han areas were enrolled. HIV prevalence in the Yi area was consistently high, ranging from 9.46% (63/666, 2011) to 2.88% (23/798, 2012) over the period from 2010 to 2016. HIV prevalence in the Han areas ranged from 0.15% (2/1333, 2010) to 0.44% (7/1604, 2011) over the same period. Multivariate logistic regression showed that unprotected casual sexual behavior, male gender, illiteracy, drug use, and injection drug use were positively associated with HIV infection risk in the Yi area. Path analysis of the risk factors revealed that casual sexual behavior (0.051) and injection drug use (0.161) were directly associated with HIV infection. However, marital status (0.004), ethnicity (0.017), education level (−0.004), HIV/AIDS-related prevention knowledge (−0.012), and drug use (0.11) had an indirect influence on HIV infection through casual sexual behavior and injection drug use. The prevalence of HIV is high among residents of majority-Yi areas, and injection drug use and casual sexual behavior are risk factors for infection.